2002
DOI: 10.1002/mrm.10140
|View full text |Cite
|
Sign up to set email alerts
|

Test‐retest reproducibility of quantitative CBF measurements using FAIR perfusion MRI and acetazolamide challenge

Abstract: The reproducibility of quantitative cerebral blood flow (CBF) measurements using MRI with arterial spin labeling and acetazolamide challenge was assessed in 12 normal subjects, each undergoing the identical experimental procedure on two separate days. CBF was measured on a 1.5T scanner using a flowsensitive alternating inversion recovery (FAIR) pulse sequence, performed both at baseline and 12 min after intravenous administration of acetazolamide. T 1 was measured in conjunction with the FAIR scan in order to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

12
78
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(90 citation statements)
references
References 34 publications
12
78
0
Order By: Relevance
“…Based on the coefficient of variation which was 7.9 % in the global GM ROI, we conclude that the reproducibility of our measurements lies well in the range reported for other pulsed (28)(29)(30) and continuous ASL (31)(32)(33)(34) methods. A recent multi center study at 3T including 28 sites (29) using a PASL method termed QUASAR (35,36) reported values for SD w in GM between 3.01 and 8.12 ml/100 g/min, which suggests that the reproducibility of our measurements is quite high.…”
Section: Discussionsupporting
confidence: 83%
“…Based on the coefficient of variation which was 7.9 % in the global GM ROI, we conclude that the reproducibility of our measurements lies well in the range reported for other pulsed (28)(29)(30) and continuous ASL (31)(32)(33)(34) methods. A recent multi center study at 3T including 28 sites (29) using a PASL method termed QUASAR (35,36) reported values for SD w in GM between 3.01 and 8.12 ml/100 g/min, which suggests that the reproducibility of our measurements is quite high.…”
Section: Discussionsupporting
confidence: 83%
“…Yen et al reported variance of PASL CBF at 1.5 T from GM ROI in a single slice (Yen et al, 2002). ROI size across subjects varied from 50 -80 cc, similar in size to our hippocampal and BA 4 ROIs.…”
Section: Discussionsupporting
confidence: 75%
“…ASL MR imaging is a safe, rapid method of measuring CBF and is applicable to the assessment of CVR. [7][8][9][10][11][12] In the present study, we evaluated cerebrovascular response to ACZ by 3D pseudocontinuous ASL MR imaging. Repeated ASL imaging after ACZ injection demonstrated a CBF increase in the whole brain visually and quantitatively.…”
Section: Discussionmentioning
confidence: 99%
“…The mean CVR values reported in normal subjects range from 25-31% with the use of 133 Xe inhalation SPECT, 18,21-23 from 33.5-35% with the use of 15 O-water positron-emission tomography, 24,25 and from 37.7-54.2% with the use of ASL MR imaging. [9][10][11] Although the CVR values obtained with the use of a PLD of either 1525 ms (43.8 -46.4%, depending on the region) or 2525 ms (26.9 -32.5%) in the present study are in the range of the reported values, those obtained with a PLD of 1525 ms as well as those previously reported by use of ASL MR imaging are relatively high; thus, ASL MR imaging probably leads to overestimation of CVR. The method that provides more accurate CVR cannot be concluded because of the lack of a standard reference; however, our results indicate that the influence of the PLD on CVR estimates should be taken into consideration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation